2019
DOI: 10.1074/jbc.ra118.005707
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin-binding protein B (FnBPB) from Staphylococcus aureus protects against the antimicrobial activity of histones

Abstract: Staphylococcus aureus is a Gram-positive bacterium that can cause both superficial and deep-seated infections. Histones released by neutrophils kill bacteria by binding to the bacterial cell surface and causing membrane damage. We postulated that cell wall-anchored proteins protect S. aureus from the bactericidal effects of histones by binding to and sequestering histones away from the cell envelope. Here, we focused on S. aureus strain LAC and by using an array of biochemical assays, including surface plasmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…We have discovered that FnBPB and ClfB are CDSN binding proteins. In addition to CDSN, the N2N3 subdomains of FnBPB bind to fibrinogen, elastin, plasminogen, and histone H3 ( 34 36 ), while ClfB N2N3 binds to fibrinogen, loricrin, and K10 ( 19 ). MSCRAMMs generally bind to ligands using the “dock, lock, and latch” mechanism ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have discovered that FnBPB and ClfB are CDSN binding proteins. In addition to CDSN, the N2N3 subdomains of FnBPB bind to fibrinogen, elastin, plasminogen, and histone H3 ( 34 36 ), while ClfB N2N3 binds to fibrinogen, loricrin, and K10 ( 19 ). MSCRAMMs generally bind to ligands using the “dock, lock, and latch” mechanism ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…This protein is involved in the primary attachment phase to fibronectin, elastin, and fibrinogen, as well as in the accumulation process in biofilm formation ( 13 , 52 ). It has also been demonstrated that FnBPB favors cell invasion and protects against the antimicrobial activity of histones released during the neutrophils extracellular traps (NETs) ( 23 , 53 ). Since we did not evaluate the presence of this marker in the other two native strains tested, we cannot discuss its influence in the invasion capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Histones have potent antimicrobial activity due to properties similar to cationic antimicrobial peptides. Histones H2A, H3 and H4 have been shown to have anti-staphylococcal activity ( Morita et al, 2013 ; Pietrocola et al, 2019 ).…”
Section: Ligands Of Fnbpa/fnbpbmentioning
confidence: 99%
“…Alternatively, FnBPB can bind to Plg which, when activated to plasmin, can cleave the sequestered histone. Also FnBPB expression was shown to be responsible for protecting S. aureus from the bactericidal effect of the total histones released by neutrophils in the form of NETs ( Pietrocola et al, 2019 ). Finally, the A domain of FnBPB can also bind to Fn by a mechanism that does not involve DLL ( Burke et al, 2010 ).…”
Section: Mechanisms Of Fnbps Interaction With Ligandsmentioning
confidence: 99%
See 1 more Smart Citation